Transformations in the models of journalists formation in Spain - Repiso Caballero, Rafael; Torres Salinas, Daniel; Delgado López-Cózar, Emilio (Estudios sobre el Mensaje Periodístico, 2012)
This is a longitudinal, retrospective and descriptive study about doctoral theses on radio which have been defended in Spain over the period 1976-2008. The TESEO database has been used to search theses and the composition of examination boards for theses on radio, even when the data had been contrasted with previous works. A number of variables have been studied to show and represent the evolution, the partnership of universities, the participants’ profiles, the academic genealogies, invisibles working parties and research teams. These are the variables studied: frequency of the terms in the titles, development of the number of thesis by year, university of thesis defense, thesis advisor, participation in examination committees and advisor-candidate genealogies. The network analysis shows the interactions among professors, level of independence, cooperation among the members in the examination boards and intermediation. The membership within the theses examination boards in Spain can be observed on the graph. It shows a mode-2 social network of advisors and universities.
Keywords: Radio; Social Network Analysis; Thesis; Dissertations; Bibliometry; Audiovisual Communication; Research.